How Does Citizen Science Compare to Online Survey Panels? A Comparison of Food Knowledge and Perceptions Between the Zooniverse, Prolific and Qualtrics UK Panels - Armstrong, Beth; Reynolds, Christian; Bridge, Gemma; Oakden, Libby; Wang, Changqiong; Panzone, Luca; Schmidt Rivera, Ximena; Kause, Astrid; Ffoulkes, Charles; Krawczyk, Coleman; Miller, Grant; Serjeant, Stephen (Frontiers in Sustainable Food Systems, 2021)
With an increasing focus on the uptake of healthy and sustainable diets, a growing body of research has explored consumer perceptions and understanding of the environmental impacts and safety of foods. However, this body of research has used a wide range of methods to recruit participants, which can influence the results obtained. The current research explores the impact of different recruitment methods upon observed estimations of the carbon footprint (gCO2e), energy content (Kcal), food safety and animal using three different online recruitment platforms; Qualtrics (N = 397), Prolific (N = 407), Zooniverse (N 601, based on unique IP addresses). Qualtrics and Prolific participants rated the carbon footprint, energy content, food safety and animal welfare of all foods in the survey. Zooniverse citizens rated the carbon footprint or energy content then food safety or animal welfare of all foods in the survey. Kruskal-Wallis and Chi-square analyses compared the energy content and carbon footprint estimations with validated values, and differences in estimate accuracy and perceptions between recruitment methods. Participants were unable to accurately estimate the carbon footprint and energy content of foods. The carbon footprint of all foods were overestimated, with the exception of beef and lamb which was underestimated. The calorie content of fruits and vegetables are typically overestimated. Perceptions of animal welfare and food safety differed by recruitment method. Zooniverse citizens rated animal welfare standards to be lower for meat products and eggs, compared to Qualtrics and Prolific participants. Overall, Qualtrics participants typically held the highest food risk perceptions, however this varied by food type. The lack of knowledge about the carbon footprint and energy content of foods demonstrates the need for consumer education and communication to enable the move toward healthier and more sustainable diets. Perceptions of food safety and animal welfare demonstrate a baseline from which to develop consumer focused communications and governance. We have shown that different recruitment tools can result in differences in observed perceptions. This highlights the need to carefully consider the recruitment tool being used in research when assessing participant knowledge and perceptions.